Academic Procrastination in Higher Education: A Meta-Analysis - Rahmawati, Diya Rofika; Wardani, Dewi Kusuma; Noviani, Leny (FKIP Universitas Lampung, 2024)
Procrastination in academia is a problem. Students are one of the academic actors who are expected to meet the needs of the global community through the skills gained from higher education institutions, to change a country's achievement of the Human Development Index (HDI). This study aims to determine academic procrastination in higher education using the meta-analysis method. The search was conducted in the Scopus database published since 1989. A total of 73 articles with a sample of 30,070 students spread across universities in 10 countries with ownership of the main HDI achievements in the world. The results of the research on academic procrastination in universities showed up to 34 low-category articles, 28 medium-category articles, 8 high-ranking articles, and 3 very high-category articles. This inconsistent condition is caused by differences in regional, geographical, environmental, and cultural conditions formed in the society of each country in the sample. The article found no publication bias, while limitations and recommendations for further research were presented. Recommendations for future research examine more deeply the factors influencing the formation of different categorizations of academic procrastination at the levels of formal, non-formal, and informal education in general, as well as certain criteria.DOI: http://dx.doi.org/10.23960/E3J/v7i2.109-122